Improving Student Learning Outcomes by Applying the Discovery Learning Model to the Acid-Base Titration Material of Senior High School - Patilima, Yunarti; Nuryanti , Siti (Universitas Tadulako, 2023)
The acid-base titration topic has links between concepts, equations of reactions, and calculations. Therefore, the lack of mastery related to this topic will affect the low learning outcomes. This study aimed to improve student learning outcomes on the acid-base titration topic by applying the discovery learning model. The sample of this study was students of class XI MIPA SMA Negeri 5 Palu, consisting of class XI MIPA 5 as experimental class 1 (n = 35) and class XI MIPA 6 as experimental class 2 (n = 33). The effectiveness of applying the discovery learning model can be seen from the average N-gain value in the experimental class. For experimental class 1, the average N-gain value was 0.67, which is included in the medium category. While the experimental class 2 was 0.63, which is included in the medium category. Based on the results of data analysis, the average value of student learning outcomes for experimental class 1 was 76.42 and experimental class 2 was 75.3. This value was greater than the average student learning outcomes before the treatment, which were 65. So it can be concluded that applying the discovery learning model can improve students’ learning outcomes in class XI MIPA on acid-base titration topics in SMA Negeri 5 Palu.